Testicular non-Hodgkin's lymphoma presenting in a young adult. (20th March 2015) - Ratkal, Vishal; Chawla, Arun; Mishra, Dilip Kumar; Monappa, Vidya
Abstract : We report a case of a 27-year-old man who presented with a slowly growing left testicular swelling associated with mild pain over a period of 3 months. He was evaluated by his family physician with scrotal ultrasound and testicular tumour markers. He was diagnosed and treated as epididymo-orchitis and managed with antibiotics. When he later presented to us, he had an enlarged left testis with normal spermatic cord. Scrotal Doppler evaluation showed a globally enlarged left testis and epididymis with increased vascularity in the left testis, with the right testis being normal. Testicular tumour markers were normal. Fine-needle aspiration cytology of the left testis was suggestive of lymphoma. Exploration through an inguinal approach was carried out and a Chevassu manoeuvre with frozen section study was performed, which was reported as non-Hodgkin's lymphoma. Left radical orchidectomy was performed. Histopathology reported diffuse large B-cell lymphoma, of a germinal centre type. Contrast CT of the abdomen, chest and brain were normal. Sperm cryopreservation was carried out. The patient was started on chemotherapy with cyclophosphamide, hydroxydaunorubicin, oncovin, prednisone (CHOP) regime.